Real effects of public country-by-country reporting and the firm structure of European banks - Eva Eberhartinger; Raffael Speitmann; Caren Sureth-Sloane (Arbeitskreis Quantitative Steuerlehre (arqus), 2020)
European regulation mandates public country-by-country reporting for banks and is expected to increase costs of tax haven activities. We hand-collect data from IFRS consolidation scopes for European banks and test whether the availability of additional public information on banks' global activity reduces their tax haven presence. In a difference-in-difference analysis, we find that indeed tax haven presence has declined significantly after the introduction of mandatory public country-by-country reporting for European banks, as compared to the insurance industry, which is not subject to this regulation. In further tests, we show that this negative association is particularly driven by a reduction of subsidiaries in "Dot-Havens" and tax havens with high financial secrecy.
Keywords: 330; country-by-country reporting; real effects; tax haven; tax disclosure